High hydrogen production rate in a submerged membrane anaerobic bioreactor. (28th September 2017) - Noblecourt, Alexandre; Christophe, Gwendoline; Larroche, Christian; Santa-Catalina, Gaëlle; Trably, Eric; Fontanille, Pierre
Abstract: Batch cultivation of an anaerobic consortium fed with glucose as sole carbon source showed a sharp decrease of the hydrogen productivity when volatile fatty acids (VFA) concentration exceeded 12.5 g L −1 . To avoid VFA accumulation, fermentative batch cultures were thereafter carried out with a submerged membrane anaerobic bioreactor to continuously remove hydrogen fermentation co-products, while retaining the biomass. The membrane made it possible to separate the residence times of bacterial biomass and hydraulic part. With this technology, average and maximal productivities reached 0.75 and 2.46 LH2  L −1  h −1, corresponding to an increase of 44 and 51% in comparison to the control, respectively. By removing the VFAs from the cultivation medium, H2 -producing pathways were favored, confirming the metabolic inhibitory effects of co-product accumulation in fermentation medium. Such hydrogen productivity is one of the highest values encountered in the literature. Readily implementable, such technology offers a good opportunity for further developing high rate hydrogen fermentation bioprocesses. Highlights: Hydrogen production using dark fermentation in batch and semi-continuous with submerged membrane anaerobic bioreactor. Consortium analysis by SSCP method. Utilization of Gompertz model to analysis hydrogen production. Determination of VFAs threshold in batch culture.